Xylazine – from a veterinary medicine to a deadly drug of abuse - Jolanta Barbara Zawilska (Farmacja Polska, 2023)
Xylazine, a potent α2-adrenergic receptor agonist, is used exclusively in veterinary medicine for its sedative, analgesic and muscle-relaxant effects. The drug is used in dogs, cats, rabbits, horses, cattle, sheep, goats, cervids, birds and laboratory animals for sedation and also to prepare for the induction of general anesthesia before surgery. Xylazine has a low therapeutic index. Exceeding the therapeutic dose two or three times may lead to the animal falling or dying due to respiratory and circulatory depression. Although the substance has never been approved for the therapeutic use in humans, over the last decade xylazine (aka “tranq” from tranquilizer) has become popular in the street drug market as an adulterant of heroin and illicit fentanyl (“tranq dope”); less frequently fentanyl analogues or new synthetic opioids that are not derivatives of fentanyl. In media reports we can also find the term "zombi drug" for xylazine. After opioids, stimulants, cannabinoids and benzodiazepines were the most common drug classes detected in conjunction with xylazine in both non-fatal and fatal intoxication cases. According to many users, xylazine may prolong the euphoric and sedative effects of fentanyl and delay the onset of withdrawal symptoms. In turn, the combined use of xylazine with cocaine or amphetamines is intended to weaken the psychostimulant effects of these drugs and symptoms of withdrawal syndrome. Use of xylazine is reported to be associated with serious cardiovascular deterioration, psychiatric and neurological symptoms, respiratory depression, hyperglycemia, and severe festering skin ulcers of the limbs with subcutaneous tissue necrosis and osteomyelitis. Xylazine is not an opioid, thus although opioids and xylazine cause similar respiratory symptoms, naloxone will not reverse the effects of xylazine overdose. Due to the fact that in Poland there is more and more media information warning about the deadly threat posed by the use of xylazine, especially xylazine combined with opioid drugs, this review is aimed to present pharmacodynamic and pharmacokinetic properties of xylazine, its toxic effects, including those in which the substance was used as adulterant of illegal drugs of abuse. Finally, treatment of xylazine overdoses and therapeutical strategies aimed to management withdrawal symptoms are discussed.